Tratamento da mastite subclínica de ovelhas no período seco com antimicrobiano convencional e antimicrobiano nanoparticulado - Santana, Raul Costa Mascarenhas [UNESP] (2014)
This study had as objectives: investigate the microorganisms that cause subclinical mastitis in meat producing sheep, define cut-off values of two methods of indirect diagnosis, compare cure rates of treatment of subclinical mastitis after intramammary infusion of antimicrobial active principle at the time of drying off in two different formulations, conventional and nanoparticle, check the rates of spontaneous cure, evaluate the capability of prevention of new infections and check the presence of antimicrobial residues in milk of sheep subjected to treatment during drying off, on consecutive lactation. The study was done in a flock located on a property in São Carlos city, São Paulo. We analyzed a total of 393 mammary glands of meat producing sheep, 250 of which belong to 130 Santa Inês breed sheep and other 143 mammary glands of 77 Morada Nova breed sheep. Milk samples were collected and submitted to California Mastitis Test (CMT), the somatic cell count (SCC) and microbiological exam before drying off and after subsequent parturition. The mammary glands with subclinical mastitis were as follows: G1 (Control, mammary glands that not received antibiotic treatment), G2 (mammary glands which was administered 100 mg of benzathine cloxacillin/ 10 mL in conventional structure) and G3 (mammary glands which was administered 50 mg benzathine cloxacillin/ 86 mL in nanocoated structure). For evaluation of treatments about their capability to prevent new infections, we used the mammary glands of healthy animals of experimentals groups groups G1, G2 and G3, and G4 was added group (healthy mammary glands, which was administered 100 mg of benzathine cloxacillin/ 172 mL in nanocoated structure). The occurrences of animals positive for infectious mastitis in Santa Ines breed sheep was 33.1% and 35.6% in Morada Nova breed sheep. Coagulase-negative Staphylococci were the predominant etiologic agents ...